(untitled) (Journal of Universal Science Research, 2025)
Brain tumors continue to present a significant challenge to modern neurosurgery due to their complex anatomical locations and the vital functions of surrounding brain structures. Traditional open craniotomy, although effective, is associated with considerable risks such as neurological deficits, infection, hemorrhage, and prolonged recovery. As medicine evolves, there has been a paradigm shift toward less invasive techniques that aim to maximize tumor resection while minimizing trauma to the patient. These methods are reshaping neurosurgical practice, making it safer and more precise.